1984
DOI: 10.1111/j.1525-1470.1984.tb01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Blindness, Anonychia, and Oral Mucosal Scarring as Sequelae of the Stevens‐Johnson Syndrome

Abstract: In its most severe form, bullous erythema multiforme is known as the Stevens-Johnson syndrome (SJS). A case of SJS is reported in which ophthalmic complications caused blindness and ultimate enucleation, and in which there occurred permanent loss of nails as well as scarring of the oral mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Nail changes occur in up to 50% of patients . Shedding of nails (onychomadesis) may occur a few weeks after the acute episode, and is due to complete nail matrix arrest during SJS/TEN. In up to 20% of patients such nail loss is permanent .…”
Section: Cutaneous Sequelaementioning
confidence: 99%
“…Nail changes occur in up to 50% of patients . Shedding of nails (onychomadesis) may occur a few weeks after the acute episode, and is due to complete nail matrix arrest during SJS/TEN. In up to 20% of patients such nail loss is permanent .…”
Section: Cutaneous Sequelaementioning
confidence: 99%
“…Acquired causes of hyponychia include trauma, onychotillomania 60 lichen planus 61 severe acrosclerosis, syringomyelia 62 Stevens–Johnson syndrome 63 and cicatricial pemphigoid 64 …”
Section: Widespread Nail Matrix Insultmentioning
confidence: 99%
“…Studies reported more than half of the TEN survivors suffered various serious long-term complications [33], including blindness [34]. In addition, there may be medico-legal consequence if testing recommendations from regulatory agencies are not followed.…”
Section: Discussionmentioning
confidence: 99%